2009
DOI: 10.1080/09603120802392884
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke and its effect on the symptoms and medication in children with asthma

Abstract: Environmental tobacco smoke (ETS) worsens asthmatic symptoms. We analyzed the relationship between levels of ETS and asthmatic symptoms and medication. We asked parents of 282 asthmatic children about the general condition, smoke exposure and medication. Patients were classified into three groups: no-ETS (no smoking), mild-ETS (smoking in the house but not in the same room as patient), and heavy-ETS (smoking in the same room as patient). We classified 116 children in no-ETS group, 124 children in mild-ETS grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…For example, environmental tobacco smoke (ETS), pollution and a high BMI have all been shown to contribute to asthma prevalence and severity. Japan has a high rate of smoking and in one study, 63.8% of asthmatic children were found to be living in households with one or more smokers [53]. In that same study, the children who were exposed to high levels of ETS had more severe asthma symptoms and needed more asthma medication compared with children experiencing less exposure, confirming the trend in many other studies of ETS worsening asthma.…”
Section: What Are the Possible Causes For The Difference In Epidemiolmentioning
confidence: 63%
“…For example, environmental tobacco smoke (ETS), pollution and a high BMI have all been shown to contribute to asthma prevalence and severity. Japan has a high rate of smoking and in one study, 63.8% of asthmatic children were found to be living in households with one or more smokers [53]. In that same study, the children who were exposed to high levels of ETS had more severe asthma symptoms and needed more asthma medication compared with children experiencing less exposure, confirming the trend in many other studies of ETS worsening asthma.…”
Section: What Are the Possible Causes For The Difference In Epidemiolmentioning
confidence: 63%
“…There was no association between symptoms and higher ETS exposure. One cross-sectional study (which was given a weak global rating) recruited 282 children with physician-diagnosed asthma and categorised them as having no, mild or heavy ETS exposure 12. The children with no and mild ETS exposure had similar symptom scores but compared with those with heavy ETS exposure had lower scores (2.3 for no and mild exposure combined vs 2.8 p=0.0048) and were at reduced risk for requiring treatment with long-acting β agonist (24% vs 43% p=0.035) and leukotriene receptor antagonist (74% vs 95% p=0.0002) compared with those with high exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Due the toxic effects of cigarette components (Yamasaki et al 2009) and other pollutant agents on the cardiovascular system (Solomon et al 2003;FukudaMatsuda et al 2007) presented in the literature, we evaluated baroreflex function in WKY and SHR exposed to SSCS during three weeks. Our exposure protocol showed that SSCS affected bradycardic reflex, tachycardic peak and HR range in WKY rats, whereas it influenced the tachycardic peak and HR range in SHR.…”
Section: Discussionmentioning
confidence: 99%